2015
DOI: 10.1002/eat.22489
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to activity‐based anorexia impairs contextual learning in weight‐restored rats without affecting spatial learning, taste, anxiety, or dietary‐fat preference

Abstract: Relapse rates are high amongst cases of Anorexia Nervosa (AN) suggesting that some alterations induced by AN may remain after weight restoration. Objective To study the consequences of AN without confounds of environmental variability, a rodent model of activity based anorexia (ABA) can be employed. We hypothesized that exposure to ABA during adolescence may have long-term consequences in taste function, cognition, and anxiety-like behavior after weight restoration. Methods To test this hypothesis we expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
16
3
Order By: Relevance
“…A study on ABA mice showed that food restriction evoked hyperactivity in the running wheel and a decrease in anxiety-like behavior in EPM and OF tests (Wable, Min, Chen, & Aoki, 2015). However, other authors were not able to show ABA-induced anxiety-like behavior in adult rats (Boersma et al, 2016;Lee and Kinzig, 2017) demonstrated that a single ABA session was not enough to induce an increase in anxiety-like behaviors in adulthood. The authors hypothesized that a cumulative effect of multiple exposures to ABA in adolescence or other stressful physiological or psychological conditions could be necessary to induce a behavioral effect.…”
Section: Discussionmentioning
confidence: 99%
“…A study on ABA mice showed that food restriction evoked hyperactivity in the running wheel and a decrease in anxiety-like behavior in EPM and OF tests (Wable, Min, Chen, & Aoki, 2015). However, other authors were not able to show ABA-induced anxiety-like behavior in adult rats (Boersma et al, 2016;Lee and Kinzig, 2017) demonstrated that a single ABA session was not enough to induce an increase in anxiety-like behaviors in adulthood. The authors hypothesized that a cumulative effect of multiple exposures to ABA in adolescence or other stressful physiological or psychological conditions could be necessary to induce a behavioral effect.…”
Section: Discussionmentioning
confidence: 99%
“…The task procedure consisted of three phases: habituation, familiarization, and test phase. Open-field analysis were conducted the day before NOR, and thereby considered as habituation to the test environment 49 . During familiarization, two objects ( A + A′ ) different in colour and size were placed in the OF arena on opposite corners with a distance of 20 cm from the walls.…”
Section: Methodsmentioning
confidence: 99%
“…Animals showed reduced ERbeta signaling in the amygdala using quantitative real-time PCR; however, ovariectomy was unable to prevent long-term behavioral changes (97). Strikingly, another study showed no effect of ABA on anxiety-like behavior as assessed using the elevated plus maze and open field test (49). Refeeding without wheel access after ABA decreased horizontal activity and exploratory horizontal behavior (13).…”
Section: Effects Of Abamentioning
confidence: 99%